Reorientasi Demokrasi Elektoral Pasca Penghapusan Presidential Threshold: Telaah Konstitusionalisme dan Siyasah Dusturiyah terhadap Desain Pencalonan Presiden - Moh Sohib; Fitri Ida Laela; Turija (ijd-demos, 2026)
Abstrak The abolition of the presidential threshold through Constitutional Court Decision Number 62/PUU-XXII/2024 marks a significant development in Indonesia’s electoral democracy. Previously, the presidential nomination threshold restricted the ability of electoral political parties to nominate presidential and vice-presidential candidates and potentially narrowed citizens’ political choices. This study aims to examine the direction of electoral democracy following the abolition of the presidential threshold from the perspectives of constitutionalism and siyasah dusturiyah. The research employs a normative legal method with a conceptual approach, focusing on the principles of democracy, limitations on governmental power, and Islamic political justice. The findings indicate that the removal of the presidential threshold strengthens the principle of equal political rights, broadens access to presidential candidacy, and reduces the dominance of party elites in the political recruitment process. From the perspectives of constitutionalism and siyasah dusturiyah, the regulation of presidential nominations should be grounded in the principles of justice, equality, deliberation, public welfare (maslahah), and limitations on power. The study implies the need for a reformulation of presidential nomination regulations that are more inclusive, non-discriminatory, and oriented toward strengthening popular sovereignty within Indonesia’s presidential system. Keywords: Presidential Threshold; Electoral Democracy; Constitutionalism; Siyasah Dusturiyah   Abstrak Penghapusan presidential threshold melalui Putusan Mahkamah Konstitusi Nomor 62/PUU-XXII/2024 menandai perubahan penting dalam demokrasi elektoral Indonesia. Sebelumnya, ketentuan ambang batas pencalonan presiden membatasi kesempatan partai politik peserta pemilu untuk mengusulkan pasangan calon serta berpotensi mempersempit pilihan politik masyarakat. Penelitian ini bertujuan menganalisis arah demokrasi elektoral pasca penghapusan presidential threshold melalui perspektif konstitusionalisme dan siyasah dusturiyah. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan konseptual terhadap prinsip demokrasi, pembatasan kekuasaan, dan keadilan politik Islam. Hasil penelitian menunjukkan bahwa penghapusan presidential threshold memperkuat prinsip persamaan hak politik, memperluas akses pencalonan presiden, dan membatasi dominasi elite partai dalam proses rekrutmen politik. Dalam perspektif konstitusionalisme dan siyasah dusturiyah, pengaturan pencalonan presiden harus berlandaskan keadilan, kesetaraan, musyawarah, kemaslahatan, dan pembatasan kekuasaan. Implikasi penelitian ini adalah perlunya reformulasi regulasi pencalonan presiden yang lebih inklusif, nondiskriminatif, dan berorientasi pada penguatan kedaulatan rakyat dalam sistem presidensial Indonesia. Kata kunci: Presidential Threshold; Demokrasi Elektoral; Konstitusionalisme; Siyasah Dusturiyah